Cooperation and the management of local common resources in remote rural communities: Evidence from Odisha, India - Ward, Patrick S.; Alvi, Muzna; Makhija, Simrin; Spielman, David J. (International Food Policy Research Institute, 2020)
It is widely recognized that local management of common pool resources can be more efficient and more effective than private markets or top-down government management, especially in remote rural communities in which the institutions necessary for the enforcement of centrally-imposed regulations may be weak or prone to elite capture. In this paper, we explore the propensity for cooperation in the management of local common resources by introducing a variant of a public goods game among remote rural communities in the state of Odisha, in eastern India. We explore various patterns of cooperation, including free riding behavior, unconditional cooperation (altruism), and conditional cooperation, in which individuals' propensity toward cooperation is tied to their beliefs about the level of cooperation among their peers. We find that a significant portion of our sample fall into this latter category, but also that their expectations about the level of contributions among their peers is somewhat malleable, and beneficial activities from external actors such as NGOs can foster increased social cohesion which increases both the level of these expectations and the manner in which these expectations are translated into subsequent cooperative behavior. We also find that cooperation is somewhat fragile, with group heterogeneity and risk in the returns to cooperative behavior posing a threat to the stability of the cooperative system.